Physiological signal analysis and open science using the Julia language and associated software - Datseris, George; Zelko, Jacob S. (Frontiers in Network Physiology, 2024)
In this mini-review, we propose the usage of the Julia programming language and its software as a strong candidate for reproducible, efficient, and sustainable physiological signal analysis. First, we highlight available software and Julia communities, that already provide top-of-the-class algorithms for all aspects of physiological signal processing, despite the language's relatively young age. Julia can significantly accelerate both research and software development due to it being a high level interactive language with high performance code generation. It is also particularly suited for open and reproducible science. Openness is supported and welcomed because the overwhelming majority of Julia software are open source and developed openly on public platforms primarily by individual contributions. Such an environment makes it more likely that an individual not (originally) associated with a software, would still be willing to put their code there, further promoting code sharing and re-use. On the other hand, Julia's exceptionally strong package manager and surrounding ecosystem allows easily making self-contained, reproducible projects that can be instantly installed and run irrespective of processor architecture or operating system.